The golden generation of Australian Soccer: understanding the factors which influenced their development - Larkin, P.; Spittle, M.; Farrow, D.; Maximos, Y.; Höner, O. (Soccer & Society, 2023)
While sporting research has focussed on the performance factors and activities contributing to elite performance, there is still limited acknowledgement of the athlete`s voice on the specific experiences and milestones that shaped their development into elite athletes. Therefore, the current study, used qualitative first-hand experiences of international level players to understand their developmental stories. In total, 17 players who represented the Australian National Soccer team during the "Golden Generation" Australian soccer (i.e. represented the Australian National Soccer Team during the Qualification period and subsequent 2006 and 2010 FIFA World Cup competitions) participated in the study. Semi-structured interviews were conducted with all participants, with the analysis identifying six key themes which described the developmental story of players. The themes included, Passion; Family; Mentality; Environment; Practice; and Pathway. The findings provide a detailed description of the environmental and socio-cultural factors the players perceived as critical in their journey to representing their nation.